Implicit and explicit attitudes towards sport among young elite athletes with high versus low burnout symptoms - Gerber, M.; Brand, R.; Antoniewicz, F.; Isoard-Gautheur, S.; Gustafsson, H.; Bianchi, R.; Colledge, F.; Madigan, D. J.; Brand, S.; Ludyga (Journal of Sports Sciences, 2019)
The development of cynical attitudes towards elite sport is a core symptom of athlete burnout and has been associated with dropout from elite sport. To date, this phenomenon has mainly been studied by investigating explicit attitudes towards sport, whereas athletes` automatic evaluations (i.e. implicit attitudes) that have been shown to influence behavior as well were not considered. This study aimed to compare explicit and implicit attitudes towards sport of young elite athletes with high (N = 24) versus low (N = 26) burnout symptoms. Using self-reported measures, general and athlete burnout symptoms were assessed. Additionally, a single-target implicit association test was administered to examine participants` automatic evaluation of sport. Statistical analysis revealed greater emotional/physical exhaustion and sport devaluation in athletes reporting high compared to low burnout symptoms. Implicit attitudes towards sport did not significantly differ between the groups. Furthermore, no significant correlations were observed between different athlete burnout symptoms and implicit attitudes. Athletes with high burnout symptoms show a tendency to explicitly detach themselves from sport, thus fostering sport devaluation as a core symptom of athlete burnout. However, this process does not seem to be reflected in their implicit attitudes towards sport.